A study of financial well-being and its key drivers in the private hospitals in East Coast Malaysia - Abd Aziz, Amirin Sofia; Ismail, Nurazleena; Wan Husin, Wan Zakiyatussariroh (International Journal of Accounting, Finance and Business, 2025)
In times of health crises and market complexity, making sound financial decisions is crucial for addressing issues related to financial well-being. Financial well-being involves having anticipated financial security, the ability to make choices, and the sustainability of desired financial freedom and living standards. This study investigates the financial well-being of private employees in the health industry on the East Coast of Malaysia, focusing on the interplay between financial literacy, money attitude, financial behaviour, and financial technology. The quantitative explanatory research was designed to investigate the financial well-being of 3500 employees from 10 private hospitals on the East Coast of Malaysia. A sample size of 381 employees was selected from two hospitals using cluster sampling. Data were collected through self-administered surveys using structured questionnaires adapted from previous studies. The data were analysed using descriptive analysis, correlation, and stepwise regression through IBM SPSS software. Descriptive statistics showed normal distribution for all scales. Correlation analysis indicated a strong positive relationship between financial literacy and financial well-being and a moderate positive relationship with money attitude. Regression analysis confirmed that financial literacy, money attitude, financial behaviour, and financial technology significantly influenced financial well-being. These findings highlight the importance of financial education and literacy in enhancing the financial well-being of private health sector employees in Malaysia.